Analisis Penerapan Standar Masyarakat Miskin di BPS Kota Binjai - Aldira Ananda; Yenni Samri Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Poverty is a condition in which a person or region is unable to improve quality of life or standard of living. Binjai cities are mentioned in a good category in the presentation of poverty compared to other cities in northern Sumatra. This study aims to find out the application of the standards of the poor society in the Central Statistical Authority (BPS) of Binjai City, using qualitative descriptive methods. The research finds that the concept used is that poverty is seen as an inability on the economic side to meet the food base not food measured on the expenditure side, and the concept is confined only to indicators of the poverty line, the presentation of the poor, the depth index of poverty, the index of misery.And there are two types of poverty data: micropoverty data and macro-poverty data.